The Effect of Finger Hold Relaxation Technique on Pain Intensity in Post-Caesarean Section Surgery Patients in the Crysant Room at dr. Abdul Rivai Hospital Berau Regency - Kiptiah, Mariatul; Purwanti, Heni; Meihartati, Tuti; Hadiningsih, Eka Frenty (Journal of Midwifery and Nursing, 2024)
Post-caesarean section surgery causes pain, which has an impact on recovery. A preliminary study of post-caesarean section surgery patients in the Crysant Room was given pharmacological treatment. Appropriate intervention is needed to minimize the effects of pharmacological use, one of which is finger-hold relaxation technique as a breathing technique that has a relaxing effect. This study aimed to determine the effect of finger-hold relaxation techniques on pain intensity. This was quasi-experimental research with a group pre-test and post-test design without a control group. The population was post-section caesarea patients in the Crysant Room at dr. Abdul Rivai Hospital Berau, with a monthly average from July to September 2023, totaling 76 people. Thirty-four respondents obtained the Lameshow formula sample. The instrument used VAS observation sheet. Data analysis used the Wilcoxon test. The pain intensity score before the finger grip relaxation technique was a median value of 8, and after the finger grip relaxation technique, the median value was 6. The finger grip relaxation technique influenced pain intensity (p-value = 0.000). This indicates that the finger-hold relaxation technique is an alternative for reducing pain non-pharmacologically in post-cesarean section surgical patients. Midwives can teach finger-hold relaxation techniques post-cesarean section patients and the benefits